(untitled) (Bangladesh Journal of Medical Science, 2018)
Objective- The infraorbital foramen is located on the maxillary bone 1 cm under the infraorbital margin. Infra orbital nerve blocks are done in children for managing the postoperative pain which can occur after cleft lip operation and endoscopic sinus operation. Infraorbital nerve can also be damaged in cases of zygomatic complex fractures which are one of the most common facial injuries. So, this study was undertaken to analyze the anatomical variations by comparing various morphometric measurements of infraorbital foramen in dry skulls of adult South Indian population. Materials and methods- 60 dry skulls of unknown sex were used for the study. Various measurements and distance from various surgical landmarks were measured to evaluate the location of infraorbital foramen on both sides. Statistical Analysis was done for the above measurements mean and standard deviation, median, range, and mode were calculated. Results: The mean distance of infraorbital foramen from piriform aperture, lower end of alveolus of maxilla and infraorbital margin was 18.39, 27.88 and 7.09mm on the right and 17.89, 27.31 and 6.95mm on the left side. The mean vertical and horizontal diameter was 3.78 and 3.50mm on the right side and 3.48 and 3.35mm on the left side. In our study, the most common site of IOF in Indian skulls was found to be in line with the second premolar tooth (59.01%), followed by its position between the first and second premolar tooth (27.87%). Conclusion- These results will be helpful for surgeons while doing maxillofacial surgery and regional block anesthesia. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.562-566